Etiological approach to chronic urticaria - Krupa Shankar D; Ramnane Mukesh; Rajouria Eliz (Wolters Kluwer Medknow Publications, 2010)
Background: In 1769, William Cullen introduced the word "urticaria" (transient edematous papules, plaque with itching). Urticaria affects 15-25% of people at least once in their life time. It is a clinical reaction pattern triggered by many factors causing the liberation of vasoactive substances such as histamine, prostaglandins and kinins. Urticaria is classified according to its duration into acute (< 6 weeks duration) and chronic (>6 weeks duration). Various clinical investigations may be initiated to diagnosis the cause. Aims: To evaluate the types of chronic urticaria with reference to etiology from history and investigations . Materials and Methods: A total of 150 patients with chronic urticaria of more than six weeks were studied. Autologous serum skin test (ASST) was performed after physical urticarias were excluded. Standard batteries of tests were performed after ASST in all patients; and other specific investigations were done where necessary. Skin prick test was done in idiopathic urticaria. Results: The study sample consisted of 62 male and 88 female patients with a mean age of 21-40 years. About 50% of patients showed an ASST positive reaction, 3.9% were positive for antinuclear antibody (ANA), IgE titer was elevated in 37%, H. pylori antibodies was positive in 26.7%. Thyroid antibodies were positive in 6.2%. Giardia and entamoeba histolytica was reported in 3.3% on routine stool examination and on urinalysis 8% had elevated WBC counts; 12% showed para nasal sinusitis, with maxillary sinusitis of 7.3%. Random blood sugar was high in 5.3%. Four patients had ASOM, two had positive KOH mount for dermatophytes, abdominal USG showed cholecystitis in two patients. Recurrent tonsillitis was noted in two patients. Urticaria following intake of NSAIDs was observed in four patients and with oral contraceptive pills in one patient. Contact urticaria to condom (latex) was seen in one patient. Cholinergic (4.7%) and dermographic (4.7%) urticaria were the predominant physical urticarias. Prick test was performed in idiopathic urticaria with maximum reactions to food antigens (25%) where brinjal was the commonest, 9% to dust in which spider web was the most common, 8% to pollen where parthenium and amaranthus were the commonest, followed by A. flavus in fungi, pigeon in epithelia and cockroach in insects. Conclusion: Nearly half of the patients had chronic autoimmune urticaria on the basis of ASST. A significant number of them had serological makers of autoimmune activity. ASST provides an easy, inexpensive investigation in CU and helps direct attention to underlying systemic auto immune diseases. The presence of these auto antibodies was significantly associated with more frequent and longer lasting urticarial attacks. Exhaustive work ups with extensive laboratory diagnostics, challenge tests, and prick testing should be reserved for individual cases following detailed history.